Youth Social Capital for the Sustainability of Halal Tourism in Setanggor Village - Feriyadin Feriyadin; Anisa Anisa; Furkan Furkan (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2022)
The development of a halal tourism village requires the role of youth social capital to ensure the sustainability of its tourism management. The purpose of this study was to identify and analyze the role of youth social capital in the development of halal tourism in tourist villages. This research was conducted in Setanggor Tourism Village, West Praya District, Central Lombok using a qualitative method of content analysis. Data was carried out by means of observation, documentation, and in-depth interviews with tourism managers in Setanggor Village.The results of this study indicate that there are several important elements that shape youth social capital, namely, social trust, self-help, collaboration, and social networks. The element of social trust is the main locomotive for encouraging youth to participate, such as: having a common identity as a Muslim who adheres to Islamic values, having an Islamic (culture) behavior, and both come from the same village. These social trust values serve as the basis for youth in increasing other elements of social capital. In an effort to maximize the strengthening of youth social capital in tourist villages, it is necessary 1) to have a meeting agenda between youth and adults in improving the quality of services such as politeness, hospitality, greetings, full of smiles, and humility of the community in serving tourists, smooth communication and information needed by tourists; 2) there is space for youth to show their existence and creativity; 3) the need for collaborative work between youth and adults through mentoring/training programs to improve the optimization of the role of youth social capital in managing and developing rural tourism. Therefore, strengthening youth social capital should be one of the strategic efforts in the context of developing sustainable halal tourism in tourist villages.